Evaluation of wheat cultivars for salinity tolerance at seedling stage based on morphological and molecular markers - Haque, Muhammad Shahidul; Mollick, Shemana; Saha, Nihar Ranjan; Begum, Shamsun Nahar (Journal of the Bangladesh Agricultural University, 2024)
Abiotic stresses are the major constraints to wheat cultivation in Bangladesh. The existence of genetic diversity for salt tolerance is a prerequisite for developing salt-tolerant wheat varieties. Evaluation of wheat cultivars under salt stress at the seedling stage was carried out in the present study using morphological and molecular markers. Twenty four cultivars were tested at 0, 6, 8, 10, and 12 dS/m salt stress in a hydroponic system. Based on morphological traits eight wheat cultivars namely Sourav, Pavon, Prodip, BARI Gom-25, BARI Gom-28, Gourav, Shatabdi and Aghrani were identified as salt tolerant because they showed a lower mean value of root length, shoot length, fresh weight and dry weight reduction at 12 dS/m of salt stress ultimately indicating a higher tolerance to salinity. According to Nei’s 1973, the highest value of gene diversity (0.9063) was observed in locus Xgwm577, and the lowest gene diversity value (0.8281) was observed in locus Xbarc84 with a mean value 0.4618. The PIC values ranged from moderate 0.4247 to high 0.8989. The highest PIC value was found in Xgwm577 and the lowest value was inXbarc84. Pair-wise comparison value of genetic distance (D) (Nei’s, 1973) between varieties was computed from combined data of 6 markers and ranged from 0.1667 to 1. Molecular marker based grouping indicates the Sub sub-cluster IIA contained ten cultivars; six tolerant cultivars (BARI Gom-25, BARI Gom-28, Prodip, Pavon, Shotabdi, Gourav), two moderately tolerant (Sonalika, BARI Gom-23) and two susceptible cultivars. We, therefore, identified six cultivars as saline tolerant at their seedling stage that clustered together in the same group when analysed by SSR markers linked to salinity. The findings of the present study have the potential for utilization in future wheat breeding for salinity tolerance. J Bangladesh Agril Univ 18(2): 234–244, 2020 https://doi.org/10.5455/JBAU.91898